Changeability, Variability, and Malleability: Sharing Perspectives on the Role of Change in Time-based Art and Utilitarian Machinery Conservation. (17th November 2021) - Wain, Alison; Sherring, Asti
ABSTRACT: This paper explores concepts of changeability, variability, and malleability in the different heritage genres of time-based artworks and utilitarian machinery. Case studies bring to the surface differences in understandings, norms, and boundaries, but also demonstrate similarities between the two areas of practice, showing that they can be viewed as poles of practice within a shared field of theory and practice rather than as separate and unrelated endeavours. The key issues for all communities caring for changeable objects are how to preserve the intangible sensory, cultural, and immersive experiences created by change, and how the practical actions required to maintain this intangible heritage interact with concepts of authenticity, performativity, and intention. This paper explores how these relationships evolve as time and contexts change, and how best practice in the conservation of changeable objects must acknowledge and manage the tension between the activation that preserves intangible, embodied experience, and the static maintenance that preserves the tangible components of an object with minimal physical change. Viewing objects through the lens of change opens the door to the development of a new field of conservation expertise, one focused on the challenges and opportunities presented by an object's changeable qualities rather than by its original field of use. A lens of change has the capacity to draw together not only those working with time-based artworks and utilitarian machinery but also other communities of people caring for and activating changeable objects, such as horologists, roboticists, musicians, car enthusiasts, people activating historic costumes, and people managing still-active historic utilities such as water and transport infrastructure.